Anagen Effluvium after Methotrexate: An Idiosyncratic Reaction - Sinha, Preema (Int J Trichology, 2020)
Low-dose methotrexate (MTX) is the backbone of treatment for extensive psoriasis vulgaris not responding to topical therapy. Since its induction for the treatment of psoriasis in the 1970, its short- and long-term side effect profile has been extensively studied. Hair loss with MTX has been reported mostly with high-dose MTX used in chemotherapy. Here, we report a case of guttate psoriasis who presented with acute-onset anagen effluvium following the administration of only two doses of MTX 7.5 mg per week.